CONSERVATION OF THE GENE POOL OF ENDANGERED ARGALI SPECIES - Sansyzbay Abylay Rysbaevich; Umitzhanov Mynbay; Bakirov Nurbol Jumakadyrov; Rysbayev Muratkhan Belderkhanovih (Academic Journal of Physical and Chemical Sciences, 2021)
Argali living on the territory of the Republic of Kazakhstan are listed in the Red Book and need special protection of the state. The number of these animals is falling every year. Urgent measures are being taken to preserve the existing species of argali in all their genetic diversity. One of the promising methods of preserving the gene pool of endangered species of wild animals is the method of deep freezing of sperm and embryo transplantation. The argali or mountain sheep species includes several subspecies that are quite well studied and differ in their external characteristics: - altai ram or Оvis аmmоn аmmоn; - anatolian mouflon or Оvis аmmоn аnаtоliса; - bukhara ram or Оvis аmmоn bосhаrеnsis; - kazakh argali or Оvis аmmоn соllium; - gansu argali or Оvis аmmоn dаlаilаmае; - tibetan mountain sheep or Оvis аmmоn hоdgsоnii; - north China mountain sheep or Оvis аmmоn jubаtа; - tianshan mountain sheep or Оvis аmmоn kаrelini; - argali Kozlova or Оvis аmmоn kоzlоvi; - karatau mountain sheep or Оvis аmmоn nigrimоntаnа; - cyprus ram or Оvis аmmоn орhiоn; - mountain ram marco polo or Оvis аmmоn роlii; - kyzylkum mountain sheep or Оvis аmmоn sеvеrtzоvi; - urmian mouflon or Оvis аmmоn urmiаnа. Conservation of biological diversity around the world is now deservedly given great attention. The problem of accelerated reproduction of genetic resources has become particularly relevant at the present time, when the Red Book is becoming larger every year, and the world around us is becoming poorer. Every year, the planet loses many species of animals and plants. Therefore, the search for conservation opportunities for endangered populations of wild animals is not only of scientific, but also of great practical interest. The theoretical basis for the conservation of rare and endangered species of wild animals in Kazakhstan has not yet been developed and has not yet been sufficiently studied. The use of biotechnological techniques makes it possible to preserve the genetic basis of valuable and endangered animal species.